Smoking: Taxing health and social security - Brian S. Armour; M. Melinda Pitts (Federal Reserve Bank of Atlanta, 2006)
While the health risks associated with smoking are well known, the impact on income distributions is not. This paper extends the literature by examining the distributional effects of a behavioral choice, in this case smoking, on net marginal Social Security tax rates (NMSSTR). The results show that smokers, as a result of shorter life expectancies, incur a higher NMSSTR than nonsmokers. In addition, as low-earnings workers have a higher smoking prevalence than high-earnings workers, smoking works to widen the income distribution. This higher tax rate could have implications for both labor supply behavior and Social Security system funding.
Keywords: H55; I1; 330; smoking; Social Security; health; taxes; widows; low earnings; Rauchen; Verteilungswirkung; Grenzsteuersatz; Arbeitsangebot; Gesetzliche Rentenversicherung; USA